2020
DOI: 10.1155/2020/2485401
|View full text |Cite
|
Sign up to set email alerts
|

Marital Status and Survival in Patients Diagnosed with Melanoma

Abstract: Introduction. Previous research suggests the presence of a spouse may considerably affect melanoma detection rates through more frequent examinations, better access to healthcare, and improved social support. Yet, the role of marital status on melanoma survival is currently unknown. The aim of this study is to assess whether marital status is associated with survival following melanoma diagnosis. Methods. We performed secondary analysis of data from all participants of the Florida Cancer Data System (FCDS) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
(20 reference statements)
0
3
2
Order By: Relevance
“…However, our result is not consistent with the results of other recent melanoma-related studies [40,41]. Scholars commonly agree that a stable marriage can enhance the likelihood of survival in cancer patients [39][40][41]. Nonetheless, it is worth highlighting that based on official 2010 data from the United States, approximately 90 million unmarried individuals aged 15 and above cohabit with a partner, in contrast to around 30 million who reside alone [39].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our result is not consistent with the results of other recent melanoma-related studies [40,41]. Scholars commonly agree that a stable marriage can enhance the likelihood of survival in cancer patients [39][40][41]. Nonetheless, it is worth highlighting that based on official 2010 data from the United States, approximately 90 million unmarried individuals aged 15 and above cohabit with a partner, in contrast to around 30 million who reside alone [39].…”
Section: Discussioncontrasting
confidence: 99%
“…It is worth noting that research examining the influence of marital status on cancer patient survival has produced diverse findings, as highlighted in the article by Aizer et al [39]. However, our result is not consistent with the results of other recent melanoma‐related studies [40, 41]. Scholars commonly agree that a stable marriage can enhance the likelihood of survival in cancer patients [39–41].…”
Section: Discussioncontrasting
confidence: 93%
“…Twenty‐two studies compared cancer specific survival in unmarried and married cancer patients, of which all but two 22 , 38 reported that married patients had a higher cancer‐specific survival rate than unmarried patients. The association was found in five studies on patients with breast cancer, 21 , 32 , 33 , 39 , 40 two studies on patients with prostate cancer 26 , 27 ; and one study each in patients with testicular, 30 head and neck, 41 gastric, 42 kidney, 34 colon, 43 oral cavity, 44 non‐metastatic urothelial bladder cancer, 45 non‐small cell lung cancer, 46 melanoma, 47 medullary thyroid, 37 colorectal 48 and liver cancer, 49 and in one study with various cancer types. 25 …”
Section: Resultsmentioning
confidence: 98%
“…In consequence, as in other primaries, more advanced age, as well as unmarried status should be considered as a potential risk factor for less favorable survival [ 36 , 37 , 38 , 39 ]. Specific social and clinical measures addressing or focusing on older patients and unmarried patients may potentially improve their survival [ 40 , 41 , 42 , 43 ]. However, due to the limited number of observations, these results cannot prompt final recommendation.…”
Section: Discussionmentioning
confidence: 99%